Substance misuse disorder in Saudi Arabia: A comprehensive examination of current demographic patterns, trends, and intervention requirements - Mansour Tobaiqy; Ahmed I. Al-Asmari (Elsevier, 2024)
Introduction: This review examines substance misuse disorder (SMD) in Saudi Arabia, drawing insights from 43 prior studies. It explores the prevalence and patterns of SMD across diverse demographics. Methodology: Our analysis integrated data from various studies involving adolescents, university students, psychiatric patients, and the general population as well as postmortem cases. It identifies key risk factors and challenges in managing SMD, underscoring the importance of comprehensive data collection for evidence-based policymaking. Results: SMD in Saudi Arabia were categorized into two groups: common traditionally abused drugs (such as Captagon, khat, heroin, ethanol, and cannabis) and substances that have emerged in recent years (e.g., methamphetamine "Shabu", pregabalin, and benzodiazepines). Trends in SMD include early substance initiation and increased amphetamine and polysubstance use. Conclusion and recommendations: Drug-related challenges persist in Saudi Arabia; however, because of limited data from recent epidemiological studies on drug disorders, the full extent is unknown. Saudi Arabia is unique because it as an Islamic country with strict regulations against drug trafficking and a religious prohibition on drugs and alcohol, which contributes to distinct trends in substance misuse disorder (SMD). Although some aspects mirror global patterns, others exhibit regional characteristics specific to the country. Despite data variability, actionable recommendations have emerged for SMD prevention and treatment. During the COVID-19 pandemic, a high number of reports was evident; however, SMD publications often reiterate old findings and overlook emerging psychoactive substances (EPS), such as 'Shabu", pregabalin, and benzodiazepines. Further studies are needed, including educational initiatives, national surveys, stricter drug regulations, and an early warning system for traditional SMD and EPS.